PKM Pengolahan Limbah Plastik Menjadi Kerajinan Fungsional Penguatan Peran Ibu-Ibu PKK di RW.15 Kelurahan Jatirahayu, Pondok Melati, Kota Bekasi dalam Rangka Mengurangi Dampak Lingkungan - hermawan, dudung; ayun, qurrota; Farudin, Tugiman (The IMPACT : Jurnal Pengabdian Kepada Masyarakat Universitas Islam As-Syafiiyah, 2025)
Plastic bottle waste is still considered a less useful waste that causes environmental pollution. However, plastic bottle waste can be utilized to create a variety of useful products. Efforts to address plastic bottle waste include recycling it to create various value-added products. This community service program aims to provide innovative solutions by utilizing plastic bottle waste into useful products, such as decorative lamps. This community service activity aims to: (1) Achieve and achieve success in the training process for making decorative lampshades from plastic waste for housewives and youth in the Jatirahayu sub-district, Pondok Melati District; (2) Build character, skills, and abilities, and develop the potential of housewives in the Jatirahayu sub-district, Pondok Melati District. This activity is conducted using a science and technology training method in the form of lectures. This activity provides skills, knowledge, and insight into creative entrepreneurship. Based on the results of observing the products produced and the growing motivation and creative entrepreneurial spirit of the training participants, this is evidenced by the various questions asked and the success of creating economically valuable products, in this case, decorative lampshades.